Controllability of second order semilinear ordinary differential systems in Banach spaces. (1999) - Balachandran, K.; Anthoni, S. Marshal
Abstract : Sufficient conditions for controllability of semilinear second order ordinary differential systems in Banach spaces are established using the theory of strongly continuous cosine families. The results obtained are based on the Schaefer theorem.